Association Between Diabetes-Related Nutrition Knowledge and Weight Status Among Cadet and Non-cadet Students at Universiti Pertahanan Nasional Malaysia (UPNM) - Zaidi, Izzatul Hareesa; Azizzul, Atiqa Nabiha; Ismail, Nazrul Hadi; Wan Ahmad Fakuradzi, Wan Farizatul Shima binti (Jurnal Gizi dan Pangan, 2024)
The aim of this study is to investigate the association between diabetes-related nutrition knowledge and body weight status among non-diabetic young adults. This cross-sectional study utilized a questionnaire assessing socio-demographic and Diabetes-Related Nutrition Knowledge-Questionnaire (DRNK-Q). Weight, height, and waist circumference were measured using standard protocols, and body weight categories were established using the Body Mass Index (BMI). Data from 320 young adults, aged 18‒26 years old, were collected from Universiti Pertahanan Nasional Malaysia (UPNM). Participants were divided into two categories based on their knowledge scores. Overall, the study's respondents exhibited low DRNK (52.8%) and high DRNK (47.2%). Majority of respondents have normal body weight (55.7%); nevertheless, there is no relationship between body weight and diabetes-related nutrition knowledge. To conclude, there is no knowledge difference between cadet and non-cadet. Therefore, public health initiatives must customize interventions suitable to support behavior and lifestyle changes based on the amount of diabetes awareness.